2021
DOI: 10.1021/acscatal.1c04208
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Transition-Metal-Catalyzed Asymmetric Reductive Amination

Abstract: Asymmetric reductive amination (ARA) of a prochiral carbonyl compound with an amine using a H2/hydrogen surrogate is a concise and operationally simple method for the synthesis of chiral amines. ARA proceeds via condensation of a carbonyl group with an amine/ammonia followed by the enantioselective reduction of the generated intermediate. The activation of reductant and stereoselective transfer of hydrogen to intermediate imine/enamine is often mediated by a chiral transition metal catalyst. Considering the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 163 publications
0
46
0
1
Order By: Relevance
“…3 Representative alternatives include transition metalcatalyzed direct asymmetric reductive amination (DARA) of carbonyl compounds with transition metal hydrides. [4][5][6] Nonetheless, while there are always exceptions, oftentimes the associated conditions tend to be harsh, waste-generating organic solvents are invariably involved, and extensive use of toxic and/or precious metals (e.g., Ir, Rh, and Ru) are the norm. This latter issue can be non-trivial, as metal contamination of the desired final product(s), by FDA standards, can be a relatively common occurrence due to catalyst loadings.…”
Section: Introductionmentioning
confidence: 99%
“…3 Representative alternatives include transition metalcatalyzed direct asymmetric reductive amination (DARA) of carbonyl compounds with transition metal hydrides. [4][5][6] Nonetheless, while there are always exceptions, oftentimes the associated conditions tend to be harsh, waste-generating organic solvents are invariably involved, and extensive use of toxic and/or precious metals (e.g., Ir, Rh, and Ru) are the norm. This latter issue can be non-trivial, as metal contamination of the desired final product(s), by FDA standards, can be a relatively common occurrence due to catalyst loadings.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric reductive amination is oen accomplished using organocatalysis [4][5][6] or chiral transition metal (TM)-based catalysis. [7][8][9][10] In an early example of the latter, Blaser showed that the precursor 1a of the herbicide (S)-metolachlor could be synthesized from methoxyacetone 1 with 2-methyl-5ethylaniline a and hydrogen using an iridium catalyst generated in situ from 2, giving the amine product (S)-1a with 78% e.e. (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…1a ). The increasing demand has driven the development of novel and efficient methods for their synthesis 1 – 3 , including two practical and highly efficient routes, asymmetric hydrogenation 4 – 9 and reductive amination 10 15 (Fig. 1b ).…”
Section: Introductionmentioning
confidence: 99%